PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING DALAM PEMBELAJARAN IPAS KELAS V MIS AWALUDDIN KUBU RAYA - Meidianti, Hesty Zenitha; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2025)
This study generally aims to develop a Discovery Learning-based Student Worksheet (LKPD) for fifth-grade elementary school students that is feasible and practical for supporting IPAS (Integrated Science) learning activities. The research employs the ADDIE method. The study participants include a homeroom teacher, 16 students from class VB at MIS Awaluddin Kubu Raya, and two expert validators, who are lecturers. The data collection technique used in this research is a questionnaire.The research results indicate that the development of the Discovery Learning-based Student Worksheet (LKPD) has gone through five stages: analysis, design, development, implementation, and evaluation. The feasibility of the developed Discovery Learning-based Student Worksheet (LKPD) was rated as